Environmental impacts on reproductive health and fertility - Woodruff, T. J. (Tracey J.) (New York : Cambridge University Press, 2010)
"Many reproductive and developmental health problems are caused by exposure to chemicals that are widely dispersed in our environment. These problems include infertility, miscarriage, poor pregnancy outcomes, abnormal fetal development, early puberty, endometriosis, and diseases and cancers of reproductive organs. The compelling nature of the collective science has resulted in recognition of a new field of environmental reproductive health. Focusing on exposures to environmental contaminants, particularly during critical periods in development and their potential effects on all aspects of future reproductive life-course, this book provides the first comprehensive source of information bringing together the arguments that are spread out among various scientific disciplines in environmental health, clinical and public health fields. It provides a review of the science in key areas of the relationship between environmental contaminants and reproductive health outcomes, and recommendations on efforts toward prevention in clinical care and public policy. - Provides information about what the common environmental chemicals are, where they come from and how people are exposed - Gives practical information for healthcare providers and extensive resources for finding more information when necessary - Provides context for the use of science and the role of health care providers in shaping public policy regionally, nationally, and internationally"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Reproductive toxicology; Reproductive health -- Environmental aspects; Reproductive Medicine; Environmental Exposure -- adverse effects; Infertility -- chemically induced